SERVICE QUALITY EFFECT AND TRUST TO THE DECISION OF UTILIZING THE SRIWIJAYA AIR FLIGHT COMPANY SERVICE - Sibagariang, Agnes B.; Prihatini, Apriatni Endang; Nurseto, Sendhang (Jurnal Ilmu Administrasi Bisnis, 2015)
The research was motivated by the increasing of competition among the competitors flight services company. Sriwijaya Airlines company was experiencing decline sales 27,05% in 2013. In this case, the company had to increase the service quality and trust to the decision of utilizing of the Sriwijaya Air flight company service.This research aims to know the service quality effect which is consists of five dimensions of service quality they are reliability, responsiveness, assurance, empathy, tangible; and trust to the decision of utilizing the Sriwijaya Air flight company service. The hypothesis is there was service quality effect and trust to the decision of utilizing the Sriwijaya Air flight company service. The type of this research is an explanatory research, the sample collecting technique is purposive sampling technique by 100 samples as the respondents. This research used linear regression which is supported by SPSS for Windows as the analysis method.The results of statistical research shows that the quality of service and trust variables have a positive influence to the decision of utilizing the Sriwijaya Air flight company service. Consumer perceptions of service quality Srwijaya Air quite good and the confidence level is high so that relatively strong consumption decisions. It can be concluded that the quality of service and trust affect the decision Sriwijaya Air service usage.Based on the results of the research, the researchers suggested that the company improve the service quality, increase flight service, compensation for damage to goods and increase consumer confidence like improve the consistency of the performance of the officer so that customers do not switch to a competitor and still survive in the competition at this time.